His brain, her brain : how divinely designed differences can strengthen your marriage - Larimore, Walt, 1952-; Larimore, Barb. (Grand Rapids, Mich. : Zondervan, 2008)
In a world where men and women are constantly told they are not different, His Brain, Her Brain shows couples what they instinctively know--men and women are different, and these divinely designed differences, when understood, make a marriage stronger and happier. Combining the latest brain research along with their experiences in over three decades of marriage and counseling, Dr. Walt and Barb Larimore explain how the unique design of each sex, particularly the unique brain and hormones of each, results in different habits, tendencies, and nuances of thought and action.
Part 1 : his brain, her brain, the science -- Different by divine design -- Different as night and day -- Part 2 : his brain, her brain, the differences -- Differences in how we perceive the world -- Differences in how we process input from our world -- Differences in how we communicate with our world -- Decoding our communication differences -- Part 3 : his brain, her brain, the impact on relationships -- Sex on the brain -- Sex by God's design -- His brain--conquest, her brain--nurture -- His brain--provision, her brain--security -- His brain--respect, her brain--love -- Part 4 : his brain, her brain, the beauty of God's design -- Created to be one by God's design -- Cherish, honor, nurture by God's design.
Includes bibliographical references (p. 207-225) and indexes.
Keywords: Marriage -- Religious aspects -- Christianity; Brain -- Sex differences; Sex differences -- Religious aspects -- Christianity; Human behavior -- Physiological aspects